Analysis of Diabetic Retinopathy Based on Texture Properties of Retinal Images - Kalita, Abhinandan (International Journal of Computer Sciences and Engineering, 2025)
Diabetic retinopathy is the prime cause of vision loss in diabetic patients. It is caused by the damage of retinal blood vessels due to prolonged diabetes. This paper investigates on some image processing operations to extract blood vessels taking five feature set based on texture properties of images for the analysis of diabetic retinopathy. The proposed method stands out prominent in terms of specificity and accuracy.